Fish as an ingredient in noodles. - Yu, S. Y.; Lee, S. Y. (1990)
Fish noodles were prepared by the incorporation of wet fish mince into wheat-based noodles. The two species of fish used were Nemipterus sp. and Oreochromis mossambicus. The noodles were assessed for odour, colour, texture and overall acceptability using two standard recipes, and were found to be acceptable up to a certain level of incorporation of the mince. Noodles containing Nemipterus sp. were rated higher than noodles with 0. mossambicus and the control sample, which contained no fish. Protein contents were higher than the control sample (11.15%). Noodles with 20% Nemipterus sp. and 0. mossambicus contained 16.01% and 16.51% protein respectively.